Empirical Study on Value Drivers of Angel Backed Start-up Companies in Bangalore - J. C., Usha; Kharvi, Abhilash (AMC Indian Journal of Entrepreneurship, 2019)
Business angels engage themselves in providing capital to nascent ventures. Startup ventures generally employ personal funds for setting up venture. In spite of sound financial ecosystem available for startups, limited number ventures attract angel investment. Most of the startups depend upon personal funds. Angel investors play key role in financial eco-system of start-ups. Angel investors hunt for high growth potential ventures for investment. The objective of this study was to identify different criteria for angel investments. This study was conducted in the leading start-up hub Bengaluru. Data were collected through responses taken from 72 angel funded startups operating in Bengaluru. SPSS exploratory factor analysis and correlation were used for identifying the key factors influencing angel investments. The study revealed that entrepreneur experience and funding obtained from earlier rounds, external finance, past experience of handling challenges, and industry knowledge were the main criteria for angel investments. Overall, results show that entrepreneurial skills play a major role in attracting angel investment.